Conformance of the food vendor carts design to the prescribed standards as per food safety and standards regulations: Assessment from an urban area of North India - Kumar Pushkar; Garima Bhatt; Madhur Verma; Sonu Goel; Amarjeet Singh (Wolters Kluwer Medknow Publications, 2022)
Background: Food Safety and Standards Authority of India, established under the Food Safety and Standards Act, 2006, is mandated with disseminating evidence-based standards, regulating the manufacture, storage, distribution, sale, and import of street food, for ensuring the availability of safe and wholesome food for human consumption and matters connected in addition to that or incidental to that. Hence, this study was conducted to ascertain the conformance of the design of street food vendor's carts to the prescribed standards. Methods: We conducted a cross-sectional study in Chandigarh between July 2017 and March 2018 among 400 street food vendors. The primary dependent variable of the study was conformance. The carts were evaluated for their conformance to the standard recommended design based upon a checklist designed using the guidelines of Food Safety and Standards Regulations, 2011. Results: Almost half of the respondents had an experience of 6-15 years (48.5%) and were earning between Rs. 500 and 1000/day (56.3%). The majority of them (95%) were migrants from other states. Only 26.3% were using mobile vending sites. On regression analysis, better cart score was predicted by age, education, increasing experience, higher income, when food was prepared at home only, and with assistance in the form of helpers. Conclusions: This study indicates that although the policy was formulated 8 years back, the standards of street food carts were still below par in Chandigarh. The government should give technical specifications and ensure uniformity at the national level.